2019
DOI: 10.1111/1753-0407.12987
|View full text |Cite
|
Sign up to set email alerts
|

The association between sleep efficiency and diabetes mellitus in community‐dwelling individuals with or without sleep‐disordered breathing

Abstract: Background Sleeping habits have been reported to be associated with diabetes mellitus. This study aimed to explore the relationship of sleep efficiency with diabetes mellitus in individuals with or without sleep‐disordered breathing based on polysomnography records. Methods We enrolled participants from the Sleep Heart Health Study. Objective indicators of sleep characteristics including sleep efficiency, sleep latency, slow‐wave sleep, wake after sleep onset, and total arousal index were monitored via in‐home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
(64 reference statements)
2
14
0
Order By: Relevance
“…In our study, hyperglycemia consists of fasting plasma glucose (FPG level) ≥ 6.1 mmol/L or Oral Glucose Tolerance Test (OGTT) 2 h plasma glucose level ≥ 7.8 mmol/L and/or previously diagnosed diabetes that was under treatment. In line with the result, a community-based cross-sectional study showed an inverse association between poor sleep efficiency and prevalence of diabetes in middle-aged and older adults [ 45 ]. Additionally, a study found that poor sleep efficiency was significantly associated with worse glycemic control among type 2 diabetic patients [ 46 ].…”
Section: Discussionsupporting
confidence: 61%
“…In our study, hyperglycemia consists of fasting plasma glucose (FPG level) ≥ 6.1 mmol/L or Oral Glucose Tolerance Test (OGTT) 2 h plasma glucose level ≥ 7.8 mmol/L and/or previously diagnosed diabetes that was under treatment. In line with the result, a community-based cross-sectional study showed an inverse association between poor sleep efficiency and prevalence of diabetes in middle-aged and older adults [ 45 ]. Additionally, a study found that poor sleep efficiency was significantly associated with worse glycemic control among type 2 diabetic patients [ 46 ].…”
Section: Discussionsupporting
confidence: 61%
“…An increased percentage of fragmented REM sleep was also correlated with depressive symptoms in adolescents ( 11 ). Moreover, objective sleep characteristics such as sleep efficiency (SE) and wake after sleep onset (WASO) were associated with human health, but little evidence was found about the association between objective sleep characteristics and depression ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia is a common sleep disorder that mainly manifests as difficulty falling asleep, difficulty maintaining sleep and frequent and early awakenings [ 1 ]. Insomnia negatively affects health and quality of life, and is strongly associated with the incidence and deterioration of diabetes [ 2 , 3 , 4 ], cardiovascular disease [ 5 , 6 , 7 ], cancer [ 8 , 9 , 10 ], cognitive impairment [ 11 , 12 , 13 ], brain damage [ 14 , 15 ] and depression [ 16 , 17 ]. In addition, blood circulation, endocrine dyscrasia, loss of immunological competence and thermoregulation are also affected by insomnia [ 18 ].…”
Section: Introductionmentioning
confidence: 99%